Prediction of Soil and Nutrient Losses from the Lake Chini Watershed, Pahang, Malaysia - Islam, Mir Sujaul; Ismail, Sahid; Muhammad Barzani, Gasim; Sahibin, Abd. Rahim; Mohd Ekhwan, Toriman (Penerbit Universiti Sains Malaysia, 2015)
Watersheds in tropical regions are frequently subjected to soil erosion and transportation of chemicals downstream. Any drastic change in land use and land cover would increase the process of land degradation. For this study, the Revised Universal Soil Loss Equation (RUSLE) was used to predict the average annual soil loss. The prediction of annual nutrient (phosphorus, potassium and magnesium) loss caused by soil erosion processes using RUSLE was also conducted. Soil and nutrient movements associated with several alternative methods of land use were studied. The rainfall erosivity (R), topographic factor (LS), land cover (C) and management factor (P) values were calculated from rainfall data together with the use of topographic and land-use maps. Soil was analysed to obtain the soil erodibility factor (K). Physical properties, such as particle size distribution, texture, hydraulic conductivity and organic matter (OM) content, were analysed to support the erosion rate analysis. The mean soil erodibility factors varied from 0.03 to 0.30 ton h MJ–1 mm–1. The annual soil loss in the study area ranged from 0.10 to 180.49 ton ha–1. Nutrient losses of phosphorus, potassium and magnesium were investigated in the study. Run-off and sediments were also analysed for these elements. The annual loss of phosphorus ranged from 0.003 to 3.23 kg ha–1, potassium from 0.10 to 8.38 kg ha–1 and magnesium from 0.003 to 2.83 kg ha–1 in the study area. A small quantity of phosphorus was present in the soil, and thus, phosphorus losses were low. The findings of the present study will help in the formulation of better conservation and management options for future land-use patterns of the Lake Chini watershed.